Medicinal plants used in treatment of various diseases in the Rwenzori Region, Western Uganda - Umba Tolo, Casim; Kahwa, Ivan; Nuwagira, Upton; Weisheit, Anke; Ikiriza, Hilda (Ethnobotany Research and Applications, 2023)
Background: The Rwenzori region is endowed with a rich diversity of medicinal plants, which are utilized by communities to treat various diseases because they are easy to access, prepare and is part of a wealth of indigenous knowledge. Despite the utilization of these plants, there is a need to systematically document plants used in the Rwenzori region, which will help in preserving indigenous knowledge and aid the process of discovering new drugs that act as agents for health promotion and disease prevention. Methods: A cross-sectional survey was conducted in the western districts of Kabarole, Kasese, Bundibugyo, and Bunyangabu with the help of semi-structured questionnaires for data collection and 24 key informants’ interviews with native herbal medicine men/women in the region. Results: Overall, seventy-seven medicinal plant species distributed in 40 families were found to be used by communities for treating over 67 diseases. The most commonly used medicinal plants included Prunus africana (Hook. f.). Kalkman (12), Hoslundia opposita Vahl (11), Bidens pilosa Linn. (11), Conyza sumatrensis (Retz.) E. Walker (9) and Ageratum conyzoides Linn. (9). The family of Asteraceae and Fabaceae made up most of the medicinal plant species used by the natives. The most used plant parts are the leaves, and boiling water is the main solvent used in the preparation of these herbal remedies, which are taken mainly orally. Conclusion: The communities of the Rwenzori region depend a lot on herbal medicine to treat various diseases irrespective of the availability of modern health care. Keywords: Ethnobotany; Asteraceae, Indigenous communities; Human diseases, Herbal medicine